Dispersive liquid-liquid microextraction methods for the determination of Triazine herbicides in aqueous samples - Abbas Ahmed, Hana Hassan (2012)
Dispersive liquid-liquid microextraction (DLLME) and dispersive liquid-liquid microextraction based on solidification of floating organic droplets (DLLME-SFO) methods coupled with gas chromatography-mass spectrometry (GC-MS) were developed for the determination of triazine herbicides in aqueous samples. Four triazine herbicides were investigated, namely simazine, atrazine, secbumeton and cyanazine. In the optimized DLLME method, a mixture of chlorobenzene (20 µL) as extraction solvent and 1 mL of acetone as disperser solvent was rapidly injected into the sample solution containing 4% (w/v) of NaCl. After 6 min centrifugation at 4000 rpm at room temperature, the fine chlorobenzene droplets settled at the bottom of the conical test tube. The settled phase (2 µL) was injected into a gas chromatograph for analysis. The DLLME method gave good limits of detection (LOD) for the selected triazine herbicides ranging from 0.1 to 0.8 µg/L and showed good linearity ranging from 0.1-1000 µg/L with coefficient of estimation (r2) of 0.999. Good enrichment factors were obtained in the range of 145-188 for most of the analytes. In the optimized DLLME-SFO method, 1-undecanol (10 µL) was mixed with 100 µL of acetonitrile as disperser solvent and the mixture was then injected into sample solution containing 5% (w/v) NaCl. After the formation of cloudy state and centrifugation for 3 min at 4000 rpm at room temperature, the mixture was separated into two phases where the fine droplets of 1-undecanol floated to the top. The test tube was then placed in ice bath for cooling and solidification. The solidified extractant was transferred into small vial where it melted and was then injected into GC-MS for analysis. The DLLME-SFO method gave low LOD ranging from 0.008-0.037 µg/L, high enrichment factors of 195-322 and good repeatability with RSD 5.1 %. The method also showed good linearity over the concentration range of 0.01-100 µg/L for all target triazines. Both methods were applied for the analysis of selected water samples and sugarcane samples. The relative recoveries of DLLME and DLLME-SFO were excellent, ranging from 96.3-130.7% and 95.7-116.9%, respectively. The results showed that the DLLME-SFO method was more efficient and sensitive than the DLLME method.